Delay in Human Neutrophil Constitutive Apoptosis after Infection with Klebsiella pneumoniae Serotype K1 - Lee, Chen-Hsiang; Chuah, Seng-Kee; Tai, Wei-Chen; Chang, Chia-Chi; Chen, Fang-Ju (Frontiers in Cellular and Infection Microbiology, 2017)
Klebsiella pneumoniae serotype K1 is a major cause of invasive syndrome defined by liver abscess with metastatic infections at other body sites. This culprit is known to be resistant to neutrophil phagocytosis and bactericidal activity. We hypothesized that K. pneumoniae serotype K1 might regulate neutrophil apoptosis and enhance the survival of the infected neutrophils that might serve as a vector for dissemination of the bacteria. Two serotypes of K. pneumoniae, KP-M1 isolated from a patient with liver abscess and DT-X (an acapsular mutant strain of KP-M1), were used to infect human neutrophils. The infected neutrophils were examined for their cytotoxicity, annexin V staining, proteins, DNA fragmentation, cytokine production, and viability that are involved in apoptosis. We found that KP-M1 was not destroyed and the ingested bacteria survived within neutrophils. While the uninfected neutrophils became apoptotic within 10 h, the neutrophils infected with KP-M1 could survive up to 24 h post infection. Constitutive apoptosis of KP-M1-infected neutrophils was significantly delayed compared to that of DT-X-infected or uninfected neutrophils (p < 0.01). KP-M1 modulated the anti-apoptotic effects by down-regulating the ratio of Bax to Bcl-2 and Mcl-1, and then delayed caspase-3 activation in the neutrophils, which was accompanied by inducing the anti-apoptotic cytokine, IL-8. These data suggest that K. pneumoniae serotype K1 can prolong the lifespan of infected neutrophils by delaying constitutive apoptosis within the first several hours of infection.